2019
DOI: 10.1038/s41598-019-54731-9
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of B7-H6 in esophageal squamous cell carcinoma

Abstract: B7-H6, a member of the B7 family molecules, participates in the clearance of tumor cells by binding to NKp30 on NK cells. B7-H6 expression level in esophageal squamous cell carcinoma (ESCC) and the clinical value remain unknown. The goal of this study was to determine the expression of B7-H6 in ESCC and further explore its clinical significance. We retrospectively collected the clinical data of 145 patients diagnosed with ESCC between January 2007 and December 2008. The expression of B7-H6 of the pathological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Among these signals, B7‐H6 /NKp30 pathway is involved in the NK cell‐mediated immune responses and tumor progression within a variety of tumors. Several previous studies demonstrated that the high expression of B7‐H6 was correlated with tumor progression and poor overall survival in some cancers (19–24, 27–29). Different research groups showed that B7‐H6 has no significant diagnostic or prognostic value in non‐small cell lung cancer and gastric cancer (26, 27).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among these signals, B7‐H6 /NKp30 pathway is involved in the NK cell‐mediated immune responses and tumor progression within a variety of tumors. Several previous studies demonstrated that the high expression of B7‐H6 was correlated with tumor progression and poor overall survival in some cancers (19–24, 27–29). Different research groups showed that B7‐H6 has no significant diagnostic or prognostic value in non‐small cell lung cancer and gastric cancer (26, 27).…”
Section: Discussionmentioning
confidence: 98%
“…B7‐H6 was also expressed in inflammatory monocytes, but not in healthy monocytes (18). Studies have reported that the expression of B7‐H6 is related to the metastasis of some cancers, and the B7‐H6 expression is negatively correlated with the overall survival (OS) rate of ovarian cancer, breast cancer, brain tumor, esophageal squamous cell carcinoma, cervical cancer, and esophageal squamous cell carcinoma (17, 19–24). However, the situation is not always the same, and it was found that the higher expression of B7‐H6 predicted favorable overall patient survival in gastric cancer (25).…”
mentioning
confidence: 99%
“…While B7-H6 is usually not expressed in normal tissues, it is commonly found in different human cancers like small cell lung cancer [107], esophageal squamous cell carci-noma [108], gliomas [109], ovarian cancer [110] or HCC [106,111], where it is associated with poorer outcome. Unfortunately, no agents modulating B7-H6 signaling on tumor or NK cells are currently available [112].…”
Section: B7-h6mentioning
confidence: 99%
“…9 B7-H6 is upregulated and associated with poor prognosis (metastasis, worse overall survival) in a variety of solid tumors, including esophageal squamous cell, gastric, small lung, and breast cancers, among others. [10][11][12][13][14] However, little is known about its expression and role in tumorigenesis of hematological malignancies, such as acute myeloid leukemia (AML). One of the few studies being that of Chretien et al, who reported that B7-H6 is expressed on the cell surface of a very small number of leukemic blasts.…”
Section: Introductionmentioning
confidence: 99%